2017
DOI: 10.1038/s41598-017-06893-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Derived Exosomes Induce the Formation of Neutrophil Extracellular Traps: Implications For The Establishment of Cancer-Associated Thrombosis

Abstract: Cancer patients are at an increased risk of developing thromboembolic complications. Several mechanisms have been proposed to explain cancer-associated thrombosis including the release of tumor-derived extracellular vesicles and the activation of host vascular cells. It was proposed that neutrophil extracellular traps (NETs) contribute to the prothrombotic phenotype in cancer. In this study, we evaluated the possible cooperation between tumor-derived exosomes and NETs in cancer-associated thrombosis. Female BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
173
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(189 citation statements)
references
References 57 publications
(82 reference statements)
8
173
0
1
Order By: Relevance
“…However, the study did not analyze the effect of tumors on thrombosis models. A second study also observed increased levels of neutrophils as well as plasma myeloperoxidase and DNA in mice with orthotopic 4T1 tumors [63]. We found increased plasma levels of G-CSF and neutrophils in nude mice with orthotopic BxPc-3 tumors [14] (unpublished data).…”
Section: Neutrophil Extracellular Trapssupporting
confidence: 57%
See 4 more Smart Citations
“…However, the study did not analyze the effect of tumors on thrombosis models. A second study also observed increased levels of neutrophils as well as plasma myeloperoxidase and DNA in mice with orthotopic 4T1 tumors [63]. We found increased plasma levels of G-CSF and neutrophils in nude mice with orthotopic BxPc-3 tumors [14] (unpublished data).…”
Section: Neutrophil Extracellular Trapssupporting
confidence: 57%
“…Leal and colleagues examined the effect of orthotopic 4T1 tumors on both arterial and venous thrombosis [63]. The presence of 4T1 tumors shortened the occlusion time in the FeCl 3 carotid artery model and a Rose Bengal/laser-induced jugular vein injury model [63].…”
Section: Neutrophil Extracellular Trapsmentioning
confidence: 99%
See 3 more Smart Citations